Effect of Cover Crop Termination Timing on Pools and Fluxes of Inorganic Nitrogen in No‐Till Corn. (1st November 2019) - Otte, Briana; Mirsky, Steven; Schomberg, Harry; Davis, Brian; Tully, Katherine
Abstract : Cover crops are increasingly used around the world to enhance N cycling and provide a suite of agroecosystem benefits. The N scavenging capacity of cover crops during winter months is well recognized. Our research characterized spring management effects (e.g., early vs. late termination) on cover crop biomass, decomposition and N release rates, inorganic soil N, soil water dynamics, and corn ( Zea mays L.) performance. Cereal rye ( Secale cereale L.) was established in Beltsville, MD, to evaluate three management scenarios: no cover crop; early termination (∼40 d before corn planting); late termination (∼7 d before corn planting). Cereal rye biomass was quantified before termination, and decomposition was tracked over a 24‐wk period to assess loss. Soil N content to 100 cm, soil volumetric water content, and corn performance were evaluated over the corn growing season. Low spring precipitation in 2016 led to similar amounts of cereal rye biomass for early and late termination; however, late‐terminated cereal rye had lower quality biomass (higher C/N) in both years, leading to slower decomposition and N release rates. Over the corn growing season, late‐terminated cereal rye consistently had smaller soil N pools, suggesting more efficient N cycling (better synchrony of N release from cover crop residues with corn N demand) than early‐terminated cover crops. Corn yields were smallest following late‐terminated cereal rye in 2016, but there was no difference in yields among cover crop treatments in 2017. Overall, we conclude that planting cereal rye cover crops and delaying termination until later in the season will help retain and efficiently cycle N while maintaining high corn yields. Core Ideas We tested the effect of cover crop termination timing on N dynamics before corn. Late‐terminated cereal rye had slower rates of biomass loss and N release. Larger soil N pools in 2017 than 2016 resulted from lower corn yields. Cover crop biomass and corn performance were influenced by precipitation levels. Nitrogen was more efficiently cycled in systems with cover crops than systems without cover crops.